A novel strategy for enhancing photoelectrochemical performance of Ca2Fe2O5 photocathodes: An integrated experimental and DFT-based approach - Yoon, Joon-Soo; Kim, Young-Min; Lee, Joo-Won; Sung, Yun-Mo (Elsevier BV, 2022)
Using a wet chemical approach, high-density Ca2Fe2O5 (CFO) nanoflakes were successfully synthesized on a NiO/FTO layer that is an effective hole transport layer (HTL). We found that a two-step annealing strategy could further increase the photoelectrochemical (PEC) efficiency of CFO photocathodes. It was elucidated that two-step annealing was beneficial in various aspects such as morphology, chemical state, optical properties, and impedance. In addition, the NiO HTL further improved the charge transport properties. The CFO on NiO HTL fabricated via two-step annealing demonstrates a photocurrent density of up to-313.7 mu A/cm(2), which is 76 % higher than that of the HTL-free CFO fabricated via single-step annealing. Through DFT calculations, it is revealed that the increase in the concentration of oxygen vacancies at the CFO surface, which was obtained by the two-step annealing process, is beneficial for lowering the relative energy throughout the hydrogen evolution reaction.